The N‐terminal fragment of Acanthamoeba polyphaga mimivirus tyrosyl‐tRNA synthetase (TyrRSapm) is a monomer in solution. Issue 6 (4th February 2013) - Choudhury, Aparajita; Banerjee, Rajat
Abstract : TyrRSapm and TyrRSapm bind by fluorescence technology (View interaction) Abstract : ► Tyrosyl‐tRNA synthetase of mimivirus (TyrRSapm ) forms weak dimers in solution. ► N‐terminal TyrRSapm (ΔTyrRSapm ) of mimivirus exists as a monomer in solution. ► The ligand‐binding affinity forl ‐Tyr and ATP is not affected in ΔTyrRSapm, but is decreased 40‐fold for tRNA Tyr .